The influence of plastic mulch degradation on microplastic contamination in agricultural soils under different climatic conditions - Muhammad Firman Azima; Mersi Kurniati; Irmansyah Irmansyah; Rofiqul Umam (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Plastic mulch is widely used in agriculture to improve crop productivity by regulating soil temperature, retaining moisture, and suppressing weed growth. However, its degradation produces microplastics that can accumulate in the soil, disrupt microbial communities, and potentially enter the food chain. This study examines microplastic contamination in agricultural soils under different climatic conditions: Bogor (humid) and Lombok (hot and dry). Various analytical techniques were employed to characterize material degradation, including FTIR spectroscopy, SEM, UV-Vis, and thermal conductivity measurements. The results show that differences in climate and environmental factors such as high temperature, UV exposure, and microbial activity can accelerate mulch degradation, resulting in higher microplastic concentrations in Lombok (455 ± 57.74 particles kg-1) compared to Bogor (265 ± 43.59 particles kg-1). FTIR analysis confirmed the presence of oxidation-derived functional groups (C=O, O-H), thermal analysis indicated a decrease in the material's thermal conductivity, UV-Vis revealed increased polymer chain scission, and SEM showed significant surface degradation. These findings highlight the environmental risks of plastic mulch use and underscore the importance of adopting more sustainable alternatives to reduce microplastic pollution in agricultural soils.